The Dynamic Model of the Slider-crank Mechanism - Horváth, Zs.; Molnárka, Gy. (Acta Technica Jaurinensis, 2013)
The paper presents a dynamic model of the slider-crank mechanism for combustion engines. The formulation is expressed by only one independent variable. The mass of the connection rod has been concentrated on two ends (two eyes). The model uses the Euler-Lagrange equation and it has been computed for numerical simulation by using MAPLE system.